Rhaponticum uniflorum (L.) and Serratula centauroides (L.) are promising ecdysteroid-containing plants - G. G. Nikolaeva; L. N. Shantanova; I. G. Nikolaeva; L. D. Radnaeva; L. L. Garmaeva; L. P. Tsybiktarova (Acta Biomedica Scientifica, 2014)
We determined promising sources of phytoecdysteroids - Rhaponticum uniflorum (L.) and Serratula centauroides (L.), growing in the Buryat Republic. Biologically active substances were founded: ecdysteroids, phenolic compounds, polysaccharides, flavonoids, tannins, saponins, vitamins.